2019
DOI: 10.1111/jocn.14940
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating holistic continuity of care for older patients: Home care nurses’ experiences using checklists

Abstract: Aims and objectives To explore home care nurses’ experiences of implementation and use of checklists developed for improving continuity of care for older patients (65+ years). Background The Norwegian Coordination Reform was implemented to improve coordination between hospitals and communities and facilitate a quicker return to home community after hospital discharge. To follow‐up, national learning networks were initialised to improve pathways for chronically ill older patients, including the development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…However, previous research has shown that CPs in general and the PaTH in particular are challenging to implement, often because of the very boundaries they are supposed to cross [8,27,41,83]. The participants' skepticism toward the checklists is supported by previous research that shows that when checklists meet the complex and messy realities of practice contexts, they are often abandoned [8,41,83].…”
Section: Crossing Knowledge Boundaries With the Help Of Checklistsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous research has shown that CPs in general and the PaTH in particular are challenging to implement, often because of the very boundaries they are supposed to cross [8,27,41,83]. The participants' skepticism toward the checklists is supported by previous research that shows that when checklists meet the complex and messy realities of practice contexts, they are often abandoned [8,41,83].…”
Section: Crossing Knowledge Boundaries With the Help Of Checklistsmentioning
confidence: 99%
“…Furthermore, recent reviews on safety and quality in care transitions [15,83] have highlighted the need to consider patient-centered knowledge sharing interventions that emphasize relationships and interaction to overcome boundaries, which is also reiterated by our ndings. Checklists may be useful for the systematization of work and as a reminder for keeping a person-centered focus across settings [27], but they should be regarded as only one aspect of a more holistic approach.…”
Section: Crossing Knowledge Boundaries With the Help Of Checklistsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no thorough scientific evaluation of patient outcomes related to introducing HCPC has so far been completed. Within the HCPC context, a qualitative exploration was conducted by Nilsen et al [ 31 ]. They studied home care nurses’ experiences with implementation and systematic use of functional and wellbeing checklists developed for improving continuity of care and quality of care in the pathways provided to old and chronically ill patients in the communities.…”
Section: Introductionmentioning
confidence: 99%
“…Continuity of care has mainly been studied from the perspective of the patient–physician relationship, where the number of contacts with the same physician over time is considered a measure of continuity (Hussey et al, 2014; Van Walraven et al, 2010). Previous studies that have focused on nurse–patient relationships in municipal home health care or neurological healthcare settings have reported that nurses can contribute to continuity of care for both patients and their next of kin (Aspinal et al, 2012; Close et al, 2013; Nilsen et al, 2019). In an ongoing project, patients and their next of kin describe nursing care as important in promoting continuity of life for patients with HF (Östman et al, 2015a, 2015b, 2019).…”
Section: Introductionmentioning
confidence: 99%